Increased red blood cell distribution width in patients with plaque psoriasis - Geat, Davide (Journal of Medical Biochemistry, 2020)
Background: Red blood cell distribution width (RDW) is frequently increased in inflammatory disorders and the magnitude of its elevation correlates with disease severity. This study was hence aimed to explore RDW values in patients with psoriasis.Methods: The study population consisted of 366 adult patients with mild to severe plaque psoriasis and 366 age- and sex-matched healthy blood donor controls. For each psoriatic patient demographic, clinical and laboratory data were regularly collected.Results: RDW and MCV were significantly higher in psoriatic patients compared to controls (13.95 vs. 13.40% and 90.4 vs. 89 fL; both p 10 and ≤ 10) in terms of RDW (p=0.36). Adopting different PASI cut-offs (i.e.  3, 5, 7, 12) did also not result in statistically significant differences (p= 0.93, 0.48, 0.22, 0.42, respectively). In linear regression analysis, no significant correlation was also found between RDW and PASI or CRP, nor with age, gender or the psoriasis comorbidities listed in Table I. Furthermore, no significant difference of RDW values was noted between psoriatic patients with and without PsA (p = 0.27).Conclusions: The results of this study confirm that RDW is elevated in psoriatic patients, though the magnitude of its increase did not appear to be associated with disease severity.